Assessment of Perceptions and Practices of the Nurses to Prevent Indwelling Catheter Associated Infection; Jinnah Hospital Lahore, Pakistan - Anwar, Ghuzala; Nawaz, Ghalib; Afzal, Muhammad; Majeed, Iram; Waqas, Ali (International Journal of Applied Sciences and Biotechnology, 2017)
Nursing is an art science and an essential health care profession in which the skilled knowledgeable persons are committed to provide care to sick peoples and strive for the, protection and promotion of health and prevention against diseases and helps to minimize the risk and risk related injuries. Urinary tract infections are very common infection in the hospital settings almost responsible for 40% nosocomial infections. All the urinray tract infection is expected that approximately more than 70% infection reported because of indewelling cathters. Objectives: To assess the perceptions of nurses regarding indwelling urinary catheter and its care. To assess the practices of nurses to prevent the indwelling catheter related urinary tract infection. Methodology: Descriptive cross sectional design and data was collected through a five point Likert scale questioner. Study population was the nursing staff from the Jinnah hospital Lahore. Sample size was 184 nurses from all indoor departments of the Jinnah Hospital Lahore. Results: The findings show that the practice and perceptions scores of the registered nurses’ in the study group are insignificant with age, qualification and experience (i.e., p-value > 0.05) with the evidence-based guidelines for prevention of catheter associated urinary tract infection. Results of study indicated insignificant relationship between registered nurses’ practice and perceptions regarding the indwelling urinary catheter associated infection. Int. J. Appl. Sci. Biotechnol. Vol 5(2): 150-158